1991
DOI: 10.1007/bf00852843
|View full text |Cite
|
Sign up to set email alerts
|

Renal venous thrombosis in infancy: Long-term follow-up

Abstract: Sixteen children (11 male, 5 female) who developed renal venous thrombosis in the neonatal period or early infancy have been followed for periods varying from 29 months to 16 years (median 12 years) after initial diagnosis. Twelve patients presented with a hyperosmolar state, and in 4 the illness was preceded by severe birth asphyxia. The diagnosis was based on the findings of clinical and/or radiological renal enlargement (15 cases), haematuria (16 cases) and elevation in plasma urea (16 cases). Thrombocytope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
52
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 8 publications
2
52
1
1
Order By: Relevance
“…14,278 Overall survival now approaches 100%. [278][279][280][281][282] Clinical sequelae in survivors include chronic renal impairment and hypertension. [278][279][280][281][282][283] Lau et al 279 reviewed all Englishlanguage reports of neonatal RVT from 1992 to 2006.…”
Section: 2-23 Renal Vein Thrombosis In Neonatesmentioning
confidence: 99%
“…14,278 Overall survival now approaches 100%. [278][279][280][281][282] Clinical sequelae in survivors include chronic renal impairment and hypertension. [278][279][280][281][282][283] Lau et al 279 reviewed all Englishlanguage reports of neonatal RVT from 1992 to 2006.…”
Section: 2-23 Renal Vein Thrombosis In Neonatesmentioning
confidence: 99%
“…Almost 80% of all RVT present within the first month and usually within the first week of life. 2,[30][31][32] Some newborns developed RVT in utero. 32 The incidence in males and females is similar, both sides are affected equally, and RVT occurs bilaterally in 24% of newborns.…”
Section: Renal Vein Thrombosismentioning
confidence: 99%
“…It is noteworthy that previous studies on renal vein thrombosis 28 and pediatric ischemic stroke 29 found a male predominance. In our cases, all female infants who had UACRT had a BW of <1 kg, whereas male infants had a wide BW range.…”
Section: Male Vulnerabilitymentioning
confidence: 82%